Innovation in Learning Arabic Reading Skills using Higher Order Thinking Skills - Aulia Mustika Ilmiani; Delima Delima (Universitas Islam Negeri Palangka Raya, 2021)
This study aims to describe Arabic Reading Skills learning activities with the HOTS (Higher Order Thinking Skill) system. The research method used is a qualitative method based on text analysis. This study indicates that HOTS-based Arabic Reading Skills learning activities categorized into three levels: Level of Analysis, Level of Evaluation, and Level of Creation. First, the Level of Analysis is oriented towards the ability of students to distinguish the form of the word Isim or fi'il from a text, distinguish and classify the position of fi'il, fa'il, or maf'ul, describe the content text using a concept map, and link main ideas or compare information about a topic from reading results. The second is the level of evaluation which is oriented towards students' ability to check or determine errors in writing letters, vocabulary, language rules, and punctuation in a text, and criticize, refute, conclude, provide reviews or reasons, and communicate reading results with different expressions. Third, the level of creation is oriented towards the ability of students to formulate a statement sentence into a question, or vice versa, reconstruct a reading text into a conversation, and produce reading results by developing thoughts or opinions into ideas or notions.